THE CORRELATION BETWEEN FAMILY SUPPORT AND ADOLESCENT'S COMPLIANCE IN JOINING THE INTEGRATED SERVICE POST PROGRAM FOR FAMILY (POSYANDU KELUARGA) AROUND THE WORK AREA OF PUBLIC HEALTH SERVICE OF AIKMEL - Marvia, Eva; Adhi, I Gusti Ayu Mirah; Mahfuz, Saupi Yaumil; Sukardin, Sukardin (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Adolescence is a transition period recognized from physical, emotional, and psychological changes happening between 10-19 years of age. Teenagers’ health problems certainly need comprehensive and integrated treatment given through IEC, counseling, peer counseling, clinical/medical services, and referrals, including the Integrated Service Post program as a form of community participation in health services. Therefore, the integrated-service-post program should be able to expand its service range; not only for toddlers, pregnant and breast-feeding women, but also other strategic targets such as teenagers and the elderly. The purpose of this study was to determine the correlation between family support and adolescent compliance in joining the family posyandu around the working area of the Public Health Center of Aikmel.This research was a descriptive correlation study using an observational approach. The population of this study was 399 teenagers and the samples were 134 drawn using systematic cluster sampling. A questionnaire was used to measure family support and observation sheets were used to find out adolescent compliance in joining the program. The data were then analyzed using the chi-square test.The results showed that the highest participation was shown by teenagers between 12-16 years of aged (70.1%) and the lowest participation was performed by adolescents aged 17-25 years (29.0%). Additionally, based on gender, girls participated more than boys (the participation of girls was 53%). Moreover, the result showed that the higher the education, the higher the family support. Finally, the levels of compliance were 53.7% (compliant) and 56.3% (non-compliant). The statistical test showed that ρ value = 0.009 (ρ < 0.05).Therefore, it can be concluded that there was a significant correlation between family support and adolescent compliance in joining the Integrated Service Post program for families around the working area of the Public Health Center of Aikmel. Hopefully, paramedics/cadres can provide counseling about the importance of family support to increase teenagers’ compliance in joining the program.